A randomized controlled trial of electromagnetic therapy in the primary care management of venous leg ulceration. - Kenkre, J; Hobbs, R; Carter, Y; Holder, R; Holmes, E (1996)
OBJECTIVE: The aim was to establish the potential efficacy, tolerability and side-effect profile of electromagnetic therapy as an adjunct to conventional dressings in the treatment of venous leg ulcers. METHOD: A prospective, randomized, double blind controlled clinical trial was carried out in a dedicated leg ulcer clinic based in one urban general practice. Nineteen patients with leg ulcers of confirmed venous aetiology were assessed. The main outcome measures were rate and scale of venous leg ulcer healing, changes in patient-reported pain levels, quality of life, degree of mobility, side effect profile and acceptability to patients and staff. RESULTS: Sixty-eight per cent of patients attending this dedicated clinic achieved improvements in the size of their ulcer (4, 21%, healed fully) and in reduced pain levels (P < 0.05) during the trial, despite the chronicity of ulcer histories. Patients treated with electromagnetic therapy at 800 Hz were found at day 50 to have significantly greater healing (P < 0.05) and pain control (P < 0.05) than placebo therapy or treatment with 600 Hz. All patients reported improved mobility at the end of the study. The electromagnetic therapy was well tolerated by patients, with no differences between groups in reporting adverse events, and proved acceptable to staff. CONCLUSIONS: Despite the small numbers in this pilot study, electromagnetic therapy provided significant gains in the healing of venous leg ulcers and reduction in pain.